39. CMAP area variability is a function of area size. Issue 4 (April 2016) - Di Sapio, A.; Melillo, F.; Bertolotto, A.; Matta, M.; Troni, W.
Abstract : We studied the relationship between CMAP area variability and CMAP area size in an experimental setting in which any other possible cause of variability was removed. In 10 normal volunteers we recorded from Abductor Digiti Minimi a CMAP of large area and one of small area simultaneously after maximal stimulation of the ulnar nerve at wrist. Ulnar nerve stimulation was repeated 5 times, 4-6 s apart, and two sets of 5 CMAPs were obtained: one of large area and one of small area. The same procedure was performed with stimulation of the ulnar nerve at the elbow. Non-polarizable, ring-shaped sintered Ag/AgCl Multitrode® surface electrodes were adopted. For each set of rectified responses (large and small) Coefficient of Variation (COV, %) was calculated. Areas and COVs from all subjects were expressed as mean ± SD. Mean intrasession variability of small CMAPs elicited at wrist was significantly greater than that of large CMAPs elicited at the same site (paired t test: p  < 0.01). Variability was even slightly greater with stimulation at elbow. These results suggest the presence of component of variability unavoidable even under optimal recording conditions that partly varies as a function of the area, being significantly greater for smaller responses than for larger ones.